Connecting ISF to ISEs for Decent Work (SDG 8): A Conceptual Framework - Syamsuri; Fina Nurafni; Ahmad Havid Jakiyudin; Mohammad Taqiuddin Mohamad (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2026)
Achieving inclusive economic growth and decent work remains a persistent challenge in many developing economies, particularly among marginalized and vulnerable groups. Therefore, this study aims to connect Islamic Social Finance (ISF) with Islamic Social Enterprises (ISEs) as a conceptual pathway for advancing Sustainable Development Goal (SDG) 8. Peer-reviewed academic and policy-oriented literature is analyzed to integrate the mechanisms of zakat, infaq, ṣadaqah, and waqf into social enterprise models using a qualitative content analysis. The results show that ISF functions as a strategic financing instrument that supports job creation, inclusive entrepreneurship, and sustainable economic participation based on the reviewed literature when used beyond consumptive charity and embedded within enterprise-based structures. Additionally, the conceptual connection between ISF and ISEs is conditioned by productive orientation, institutional integration, and governance quality. An integrative theoretical framework is proposed to connect ISF instruments, ISE operational mechanisms, and SDG 8 targets, offering insights for policymakers, ISF institutions, and social enterprises seeking to promote decent work and inclusive economic growth.